Genetic associations with plasma B12, B6, and folate levels in an ischemic stroke population from the Vitamin Intervention for Stroke Prevention (VISP) trial - Keene, Keith L.; Chen, Wei-Min; Chen, Fang; Williams, Stephen R.; Elkhatib, Stacey D.; Hsu, Fang-Chi; Mychaleckyj, Josyf C.; Doheny, Kimberley F.; Pugh, Elizabeth W.; Ling, Hua; Laurie, Cathy C.; Gogarten, Stephanie M.; et al. (Frontiers in Public Health, 2014)
B vitamins play an important role in homocysteine metabolism, with vitamin deficiencies resulting in increased levels of homocysteine and increased risk for stroke. We performed a genome-wide association study (GWAS) in 2,100 stroke patients from the Vitamin Intervention for Stroke Prevention (VISP) trial, a clinical trial designed to determine whether the daily intake of high dose folic acid, vitamins B6 and B12 reduce recurrent cerebral infarction. Extensive quality control (QC) measures resulted in a total of 737,081 SNPs for analysis. Genome-wide association analyses for baseline quantitative measures of folate, Vitamins B12 and B6 were completed using linear regression approaches, implemented in PLINK. Six associations met or exceeded genome wide significance (P≤5x10-08). For baseline Vitamin B12, the strongest association was observed with a non-synonymous SNP (nsSNP) located in the CUBN gene (P=1.76×10-13). Two additional CUBN intronic SNPs demonstrated strong associations with B12 (P= 2.92×10-10 and 4.11×10-10), while a second nsSNP, located in the TCN1 gene, also reached genome-wide significance (P= 5.148×10-11). For baseline measures of Vitamin B6, we identified genome-wide significant associations for SNPs at the ALPL locus (rs1697421; P= 7.06×10-10 and rs1780316; P= 2.25×10-08). In addition to the six genome-wide significant associations, nine SNPs (two for Vitamin B6, six for Vitamin B12, and one for folate measures) provided suggestive evidence for association (P≤10-07). Our GWAS study has identified six genome-wide significant associations, nine suggestive associations, and successfully replicated five of 16 SNPs previously reported to be associated with measures of B vitamins. The six genome-wide significant associations are located in gene regions that have shown previous associations with measures of B vitamins, however four of the nine suggestive associations represent novel finding and warrant further investigation in additional populations.